Nutrition education and its relationship to body image and food intake in Asian young and adolescents: a systematic review - Pushpa, Baladandapla Shivappa; Abdul Latif, Siti Norhedayah; Sharbini, Sharimawati; Murang, Zaidah Rizidah; Ahmad, Siti Rohaiza (Frontiers in Nutrition, 2024)
Background The literature brings to light the unhealthy nutritional habits prevalent among Asian adolescents and their high level of body image dissatisfaction. This study aims to conduct a systematic review of the literature on the effect of nutritional education interventions on their nutritional knowledge and food intake behavior, attitude, practice, and body image. Methods We searched relevant published studies in PubMed, Web of Science, Scopus, Science Direct, and Springer using the PICO framework and performed a quality assessment using the 10-point checklist adapted from the National Institutes for Health tool. Results The majority of the nutritional education interventions improve unhealthy food intake and body image misperception, particularly on nutritional knowledge/self-efficacy, healthy dietary habits, physical activities, and fruit and vegetable intake. We also found a negative association with excess weight gain, obesity, and unethical weight reduction practices, leading to dissatisfaction with body image. Conclusion These interventions can help address dietary problems and body image perception and support the development of future interventions.